Experimental performance of novel cost – effective hybrid composite slabs made with cementitious composite. (December 2022) - Singh, Maninder; Saini, Babita; Chalak, H.D.
Highlights: Introduced a new design system to make cementitious structural elements. Novel hybrid composite slabs prepared with a combination of SCC and HECC. Reduce the environmental impact of cementitious mixes by utilizing the stone waste. Design of HC slabs improved the flexural and ecological performance. Performance index (PI) method adopted to select the most preferable slab members. Abstract: The present research investigation introduced a new design system for making cementitious structural elements. This study emphasizes on novel hybrid composite slab elements. The combination of newly formed hybrid fiber reinforced engineered cementitious composite (HECC) and self-consolidation concrete (SCC) was used to make slabs. The main objective of this study was to introduce novel kind of cost effective and greener HECC structural elements. In this study total 13 types of slabs were casted based on the 7 different cement mixes. To analyse the behaviour of slab specimens cracking loads, load-deflection behaviour, energy absorption capacity, flexural strength capacity, general failure pattern, ecological and economical aspects was recorded. The results from current experimental approach depicted that new composite slab system enhanced the flexural performance, energy absorption, service life and ductility of slab specimens. Construction of slabs with HC approach reduced the global warming potential (GWP), embodied energy (EE) and cost by 16.98%, 36.1%, and 67.53% respectively than full depth PVA fiber reinforced slab (HECC1). PI method indicated that HC-SL6 slab members most preferable for flexural strength capacity, ultimate load, environmental and economical aspects.